VD_FINDINFO Jug / 2017 / 135 vom 17. November 2016 - VD Tribunal cantonal (2016)
PREUVE ILLICITE, MOYEN DE PREUVE | 197 al. 1 let. c CPP (CH), 269 CPP (CH), 273 CPP (CH), 398 al. 2 CPP (CH), 406 al. 1 let. a CPP (CH)